ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KETIDAKTEPATWAKTUAN PELAPORAN KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK TAHUN 2012 - Liestya Oktarini, Ni Made; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
Financial reporting is not timely to the public because the company went public had passed the time limit set by the Securities and Exchange Commission . This research aims to examine the impact of  firm's reputation , profitability , firm size , audit committee competence and industry classification on late publication of financial report on Indonesia Stock Market in 2012 . Judgment sampling is used to select the sample so as to obtain 39 companies . Multiple linear regression was used as a data analysis technique. The results show that firm 's reputation , profitability , firm size, competence of the audit committee affect  the late publication of  financial reports of companies listed on Indonesia Stock Market in 2012.  Other variable, the industry classification do not affect the late publication.
Keywords: Firm reputation , profitability , the size of the company , the audit committee competence, industry classification